LANGUAGE STYLES OF TEENAGE INSTAGRAM USERS IN PAKISTAN: ANALYZING CASUAL COMMUNICATION PATTERNS (Al-Aasar, 2025)
This paper examines the language styles of teenage Instagram users in Pakistan, focusing on communication patterns that reflect cultural, social, and linguistic dynamics. Style refers to the variation in language use based on the degree of formality or informality of a situation. To collect data, the researcher analyzed posts and stories of teenage and pre-adult Instagram users using a qualitative research approach (Creswell, 2014). The study explores how language is used in captions, comments, and direct messages, highlighting the influence of globalization, regional dialects, and social identity. The analysis revealed that the most common language style used by Instagram users in Pakistan is casual, reflecting the interaction between local linguistic norms and global digital culture.